Karakter Morfologi dan Sitologi Bunga Pepaya Merah Delima - Noflindawati Noflindawati; Aswaldi Anwar; Yusniwati Yusniwati; Agus Sutanto (Jurnal Biologi Universitas Andalas, 2019)
The papaya plant has three types of flowering, male flowers, female flowers, and perfect flower (hermaphrodite). The difference in interest affects the shape of the resulting fruit. This study aimed to characterize morphology and cytology of papaya flowers. The study was conducted in Tropical Fruit  Research  Institute at Solok and Laboratory of SPT at the Biology Department of the Faculty of Mathematics and Natural Sciences, Andalas University, Padang, West Sumatra. The research material uses papaya flowers Merah Delima variety  from KP. Aripan Balitbu Troipka. The results showed the male flowers of male plants were smaller than the male flowers of the perfect plant. The difference of hermaphrodite flower of pentandria with hermaphrodite elongata flower, among others, the number of stamens, the length of the stem and the size of the ovary. Hermaphrodite pentandria has a number of stamens 5 while elongata has stamens 10